Profile of Male Smoking in Rural: Descriptive Study of Timbuseng, Gowa Regency - Ismaniar, Nur Inayah; Samsiana; Rahman, Irwandi (Universitas Mandala Waluya, 2024)
Rural areas have different characteristics compared to urban areas, such as lower education levels, limited access to health information and services, and strong social and cultural influences on smoking behavior. These factors may influence smoking behavior patterns among villagers, where smoking is often more socially and culturally acceptable. This study aimed to describe community smoking behavior in Timbuseng Village. This study used a quantitative descriptive design. The population of this study was the entire Timbuseng Village population of 2,054 men, with a sample of 226 people who engage in smoking activities selected using an accidental sampling technique. The description of the smoking behavior of the male community of Timbuseng Village is primarily farmers, education level, low economic status, and choose filter cigarettes in their smoking activities; most families in Timbuseng Village have fathers and children who have the status of smokers at the same time. Smokers in Timbuseng Village have carried out their daily activities as farmers, with an open environment or outside the building motivating farmers to smoke. Hopefully, this research will be developed to improve the analysis of factors influencing male smoking behavior in Timbuseng Village.